Granzyme B+ CD4+ T cells associate with an unstable plaque phenotype in advanced human atherosclerosis. (10th June 2022) - Depuydt, MAC; Smit, V; Lozano Vigario, F; Bernabe Kleijn, MNA; De Vries, MR; Quax, PHA; Wezel, A; Smeets, HJ; Kuiper, J; Foks, AC; Bot, I; Slutter, B
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): The Dutch Heart Foundation Cytotoxic CD4+ T cells have previously been found in peripheral blood of patients with coronary artery disease (1), however their occurrence in atherosclerotic plaques and their association with the pathophysiology of atherosclerosis has not been established. Single-cell RNA sequencing was performed on human carotid atherosclerotic plaques of 18 patients to identify specific T cell populations (2). Next, human femoral and carotid atherosclerotic plaques (n=95) and matched blood samples (n=49) were analyzed by flow cytometry for the presence of CD4+GZMB+ T cells. Plaque morphology was assessed by Movat's Pentachrome staining. A distinct cytotoxic GZMB+ PRF1+ CD28- CD4+ T cell cluster was identified using single-cell RNA sequencing. Furthermore, flow cytometry analysis showed that the percentage of GZMB+CD4+ T cells was significantly elevated in plaque compared to blood (Blood: 12.17±2.0 vs. Plaque: 17.40±1.0; P=0.0002). Moreover, a significant positive correlation was observed between the percentage of GZMB+CD4+ T cells in blood versus plaque (P=0.031). In line with the proinflammatory character of these cells, we found a positive association of GZMB+CD4+ T cells (P=0.036) with necrotic core size, whereas no correlation was found with this subtype in the circulation. In this study we have shown an enrichment of cytotoxic CD4+ T cells in atherosclerotic lesions, which positively correlate with necrotic core size. Future studies are aimed at elucidating the role of these cells in advanced atherosclerosis.